Transforming Distance Education: Pedagogical Challenges and Implications - Peramita, Risna; Sriati, Sriati; Amelia, Nia; Wahyudi, Hendra; Erinawati, Erinawati (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
The changes in the educational landscape caused by the COVID-19 pandemic have driven massive transformations in the learning and teaching processes, particularly through the implementation of distance learning models. This article aims to review the nature of learning and teaching in the context of distance learning, as well as explore the challenges and implications that arise for students, educators, and educational institutions. Using a qualitative method with a content analysis approach, this study highlights that learning in the context of distance learning requires greater independence, digital literacy, and emotional engagement from students. On the other hand, learning is no longer merely a process of delivering material, but has become a dynamic technology-based interaction that requires adaptive pedagogical strategies and empathy from educators. The main challenges identified include limited access to technology, low learning motivation, and the digital divide. The implications are that educational institutions need to formulate responsive policies and redesign curricula and learning methods that align with the characteristics of distance learning. This article recommends the importance of redefining the nature of learning and teaching within a more inclusive and flexible framework, ensuring education remains meaningful and effective in the digital age.